(untitled) (University Arena, 2025)
Background. Adventure activities have been part of the physical education lessons of other countries for a long time now, yet they are still missing from the Romanian curriculum, despite the fact that it has been proved they help in the character development of the participants. Objectives. This paper analyses the effects of a modul based on initiatives and low rope activities (activities specific to adventure education) on the development of the dynamic and static balance on a group of 10-12 years old students. Methods. The adventure education module was implemented on students learning at a private school in Cluj –Napoca between November 2016-March 2017 during an extra hour of physical education that they had every week. The control group had an extra hour of physical education every week as well but they have done tipical physical education activities instead. The testing of the students was done before and at the end of the program for both groups, usingJohnson’sModified BASS Test for Dynamic Balance. Results.The results have shown a semnificative increase in the dynamic balance of the experiential group while no semnificative results were recorded for the control group. Furthermore, theaverage score of the static balance of the experiential group has shown a significantly greater increase compared to the control group. Conclusion. We can conclude that this type of adventure activities (initiatives and low rope activities) help with the development of both dynamic and static balance when used with students age 10-12 years old, and as such they have their place in the arsenal of the physical education teacher at least for the development of those abilities.